The Role of Legal System and Socioeconomic Aspects in the Environmental Quality Drive of the Global South - Alola, Andrew Adewale; Dike, Glory Chiyoru; Alola, Uju Violet (Springer, 2022)
The increasing environmental challenges associated with the Global South is potentially associated with the socioeconomic changes amid potential institutional deficiencies such as the weak or inefficient environmental regulation. Thus, this twenty-first century challenge has increasingly necessitated more climate action from the Global South as championed by the developed economies. On this note, examines the environmental aspects of law and order (LO) vis-à-vis legal system and socioeconomic (SE) indexes of the Political Risk Services for a panel of 80 selected Global South countries over the period 1984–2014. Additionally, by employing the economic growth vis-à-vis the Gross Domestic Product per capita (GDPC) as additional explanatory variable, the study employs the more recent experimental techniques of Mean Group Estimator (MG), the Augmented Mean Group Estimator (AMG) and the Common Correlated Effects Mean Group (CCEMG). Importantly, with the more efficient CCEMG, the study found that the strength of the legal system in the Global South (although not statistically significant) is a crucial factor to mitigated carbon emission in the panel countries. However, the study found that an improved socioeconomic condition and economic expansion is detrimental to the Global South’s environmental quality. Furthermore, the Granger causality result implied that each of LO, SE and GDPC exhibits a feedback relationship with carbon emissions. Hence, the study suggests the need for a stronger implementation of environmental regulations through a revitalized legal system and some concerted socioeconomic policies that address poverty and unemployment among other factors.
Keywords: Environmental quality; Global South; Legal system; Socioeconomic; sustainable development; fi=Taloustiede|en=Economics|